Congenital nasolacrimal duct obstruction: caesarean section vs. vaginal delivery - Aydın Yildiz (Medicinski glasnik, 2018)
Aim: To investigate the association between the incidence of congenital nasolacrimal duct obstruction (CNDO) and delivery by caesarean section or spontaneous vaginal labour. Methods: A total of 40 patients who were diagnosed as CNDO and treated with lacrimal probing between January 2011 and February 2013 were reviewed retrospectively. The patients were divided into two groups: group 1 (caesarean section delivery) and group 2 (spontaneous vaginal delivery). Results: A total of 22 patients delivered by caesarean section (group 1) were compared with 18 patients delivered by spontaneous vaginal labour. There were 10 male (45%), 12 female (55%) patients in group 1 and nine (50 %) males, nine females (50 %) patients in group 2. The mean age of group 1 was 14.85 months (12-22 month) and group 2 was 15.20 months (12-23 month). Mean birth time was 38.1 week (36-40 week) in group 1 and 39.4 week (38-41 week) in group 2. There was no statistically significant difference between the age, gender and birth time between the groups (p>0.05). There was no statistically significant difference between the way of delivery (caesarean section or spontaneous vaginal delivery) and the incidence of CNDO (p>0.05). Conclusion: Congenital nasolacrimal duct obstruction was found less frequently among the patients delivered by vaginal delivery comparing to the patients with caesarean delivery, however this difference was not statistically significant. It is considered that, with the studies which include more patients, the difference may become significant.
Keywords: epiphora; probing; nasolacrimal duct obstruction; congenital